Rola przeciwciał przeciw pericytom ściany naczyniowej w rozwoju retinopatii cukrzycowej - Adamiec, Joanna; Oficjalska-Młyńczak, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Diabetic retinopathy is one of the most common devastating complications of diabetes. Pericyte loss, microaneurysms and acellular capilllaries are characteristic for the diabetic retina. Researches have provided evidence that hyperglycaemia is one of the main factors driving the onset and progression of diabetic retinopathy. Although it has been shown that tight metabolic control has beneficial effects on the development and progression of this complication, the increase of blood glucose concentrations does not account for all the risk for development and progression to sight threatening retinopathy. A number of reports suggest that autoimmune mechanism play a role in diabetic microangiopathy (circulating antiendothelial cells autoantibodies, antiphospholipid antibodies, presence of immunoglobulins, lymphocytes and cytokines in diabetic retinal tissue). Diabetic subjects were also found to have autoantibodies to microvascular pericytes in their circulation. These results may contribute to understanding why retinopathy progresses in some patients, despite consistent reduction of blood sugar. This publication tries to estimate the anti-pericyte autoantibodies role in progression of diabetic retinopathy.